Clinical significance of proliferative inflammatory atrophy finding in prostatic biopsies. Issue 14 (17th July 2015) - Servian, Pol; Celma, Ana; Planas, Jacques; Placer, Jose; de Torres, Inés M.; Olivan, Mireia; Morote, Juan
<x xml:space="preserve">Abstract</x> Background Proliferative inflammatory atrophy (PIA) has been involved in prostatic carcinogenesis. However, little is known about the clinical significance of a PIA finding in prostatic biopsies (PBs). The aim of this study is to determine the incidence of prostate inflammatory atrophy (PIA) in prostate biopsies (PBs), its association to high‐grade prostatic intraepithelial neoplasia (HGPIN), prostate cancer (PCa), and tumor aggressiveness. Methods Prospective and observational study of PIA lesion in 528 extended PBs and 200 radical prostatectomy specimens (RPS). Outcome measurements: PIA, HGPIN, PCa incidence, Gleason score, clinical and pathologic tumor stage and insignificant tumor rate. Univariate and multivariate analysis. Results Overall incidence of PIA and HGPIN was 30.3% and 54%. In RPS, the incidence was 30.5% and 72%, respectively. No significant association was found between PIA and HGPIN. Overall PCa detection rate in PBs was 38.1%. PCa was found in 27.5% PBs with PIA and 42.7% of those without PIA, P < 0.001. In contrast, PCa was detected in 50.9% of PBs with HGPIN and 23% of those without HGPIN, P = 0.001. Multivariate analysis revealed that PIA decreased the risk of PCa, OR:0.59 (95%CI:0.37–0.95), P = 0.029, while HGPIN increased OR:3.16 (95%CI:2.04–4.90), P = 0.001. PIA was not related to Gleason grade and clinical stage, however it was associated to an insignificant tumors increase, OR:3.08 (95%CI:1.09–8.7), P = 0.033. The information in RPS suggests that PIA is associated with less aggressive tumors and a higher probability of insignificant tumors. Conclusions PIA is present in one third of PBs, HGPIN in one half of them, and no association exists between both lesions. Contrary to HGPIN, PIA finding is associated to lower risk of PCa detection. Tumors accompanying PIA seem to be less aggressive and have a greater probability of being insignificant. Prostate 75:1669–1675, 2015. © 2015 Wiley Periodicals, Inc.